Variabilitas Peubah Tanah Tambak Budidaya Udang - Anugriati, Anugriati; Elviana, Sisca (AGRICOLA, 2020)
Variability of pond soil variables has an important role in many bio-environmental systems includingthe pond environment. This study aims to determine the variables of pond land. Determination ofmeasurement points and soil sampling is done randomly at 67 sample points. A total of 11 soilchemical characteristics were measured in the field and analyzed in the laboratory. The resultsshowed that in general, the type of soil in the pond area was alluvial soil with non-sulfuric acid. Theaverage negative potential for pond soil redox is -102 mV. The C-organic content of pond soil variesfrom 0,51 to 2,72% with an average of 1.60%, the PO4 content in pond soil is classified as low,between 3,27 and 53,01 ppm with an average of 20,75 ppm, meanwhile, the content of toxic elementssuch as Fe and Al in the ponds is classified as low, with an average of 529,6 and 205,0 ppm